Antimicrobial potential of ag-doped ZnO nanostructure synthesized by the green method using moringa oleifera extract. Issue 3 (June 2020) - Swati; Verma, Ritesh; Chauhan, Ankush; Shandilya, Mamta; Li, Xiangkai; Kumar, Rajesh; Kulshrestha, Saurabh
Graphical abstract: Abstract: Novel properties of green synthesis have paved a new area of research amongst the scientific community. In the present study, a systematic investigation has been carried out to synthesize highly oriented and uniform Ag-doped ZnO nanostructures using the extract of Moringa oleifera (MO). The structural and morphological characteristics of synthesized nanostructures were investigated using XRD and FESEM. The crystallite size was calculated to be 54.1 nm and 36.187 nm with the Scherrer method and Williamson-Hall method, respectively. FESEM confirms the flower-like structure of the nanostructures and EDX analysis confirmed the presence of Silver (Ag), Zinc (Zn), and Oxygen in the synthesized sample. TEM images reveal the continuous planes of the crystal and confirm the high crystallinity of the sample. Antimicrobial activities were analyzed against different human pathogenic bacteria, ( i.e., Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, MRSA, Salmonella typhii, Klebsiella pneumonia ), yeast ( Candida albicans) and plant pathogenic fungus ( i.e., Fusarium spp., Sclerotinia sclerotiorum, and Rosellinia necatrix ). Nanostructures showed maximum inhibition zone against Staphylococcus aureus (17 mm) as compared to other bacteria and showed 18 mm inhibition zone against C. albicans . Nanostructures showed growth inhibition of 56.8 %, 34.78 % and 48.9 % Rosellinia necatrix, Fusarium spp. and Sclerotinia sclerotiorum, respectively. The antimicrobial activity of Ag-doped ZnO was observed to be effective. The present work gave a conceivable method to develop nanostructures with desirable properties to be applied in antimicrobial activities.